2013
DOI: 10.1029/2012je004151
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and morphology of geologic units at Libya Montes, Mars: Ancient aqueously derived outcrops, mafic flows, fluvial features, and impacts

Abstract: [1] There is ample evidence of both ancient and long-lasting fluvial activity and chemical alteration in the Libya Montes region south of Isidis Basin. The region hosts Noachian to Amazonian aged surface rocks with extensive outcrops of olivine-and pyroxene-bearing material. Libya Montes also features surface outcrops and/or deposits hosting Fe/Mgsmectite, Fe/Mg-smectite mixed with carbonate and/or other Fe/Mg-rich phyllosilicates, and Al-smectite. These units likely formed through chemical alteration connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 63 publications
9
83
0
Order By: Relevance
“…In terms of alteration products, studies report detections of phyllosilicates Fraeman et al, 2009;Loizeau et al, 2012) in impact craters using CRISM data. Carbonates have been detected at the northern border of our investigation area in Libya Montes (Bishop et al, 2012(Bishop et al, , 2013Ehlmann et al, 2008), in Leighton crater (Michalski and Niles, 2010) and around Huygens crater (Wray et al, 2011). Glotch and Rogers (2013) report detections of lime (CaO), periclase (MgO), portlandite (Ca(OH) 2 ), and brucite (MgO) near Syrtis Major.…”
Section: Geological Setting and Crustal Outcrops Between Hellas And Imentioning
confidence: 92%
“…In terms of alteration products, studies report detections of phyllosilicates Fraeman et al, 2009;Loizeau et al, 2012) in impact craters using CRISM data. Carbonates have been detected at the northern border of our investigation area in Libya Montes (Bishop et al, 2012(Bishop et al, , 2013Ehlmann et al, 2008), in Leighton crater (Michalski and Niles, 2010) and around Huygens crater (Wray et al, 2011). Glotch and Rogers (2013) report detections of lime (CaO), periclase (MgO), portlandite (Ca(OH) 2 ), and brucite (MgO) near Syrtis Major.…”
Section: Geological Setting and Crustal Outcrops Between Hellas And Imentioning
confidence: 92%
“…In fact, Mg-rich carbonates are often observed together with Ferich smectites and were in many cases difficult to completely isolate from the Fe-smectite signatures (e.g. Ehlmann et al, 2009;Bishop et al, 2013). Likewise, it would not be surprising if ancient chloride deposits (Osterloo et al, 2010) are rich in Mg.…”
Section: Connections To Protoliths and Processesmentioning
confidence: 95%
“…Considering that our classification of clay minerals on Mars is focused on Fe-content, it makes sense to compare the geographic occurrence of different groups to the Fe-content of the Martian crust, as observed in Gamma Ray Spectrometer (GRS) data (Boynton et al, 2008) (Fig. 8b).…”
Section: Global Occurrences Of Smectitic Clay Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg-Fe carbonate has been inferred from multiple instruments on the Spirit rover in the Comanche outcrop within Gusev crater (Morris et al, 2010), and by the Curiosity Rover in Gale Crater in low abundance (Leshin et al, 2013;Archer et al, 2014;Ming et al, 2014). Regional deposits of Mg-or Mgand Fe-carbonate have been observed in Nili Fossae and Huygens crater (Wray et al, 2011), Ca-or Fe-carbonates have been exhumed by a crater near Syrtis Major (Michalski and Niles, 2010) and in McLaughlin Crater (Michalski et al, 2013), and small amounts of dolomite has been identified in Libya Montes (Bishop et al, 2013a). With the exception of the global dust component and a potentially regional process germane to the carbonate discovered by the Phoenix lander, all of the carbonate deposits found on Mars to date are both rare and localized.…”
Section: Introductionmentioning
confidence: 97%